Habitat associations with counts of declining Western Grebes in Alberta, Canada - Mara E. Erickson; Christine Found-Jackson; Mark S. Boyce (Avian Conservation and Ecology, 2017)
During the past several decades, numbers of Western Grebes (Aechmophorus occidentalis) have declined throughout their breeding and wintering ranges in North America. We estimated Western Grebe abundance and documented habitat factors between 2007 and 2009 from 43 lakes in Alberta, Canada where Western Grebes historically have occurred, to (1) compare Western Grebe abundance with the relative probability of persistence, and (2) identify habitat correlates of grebe abundance. The relative probability of Western Grebe persistence was correlated with abundance in the study area, although only 19% of the variation in persistence probability was explained by abundance. Western Grebe abundance was positively correlated with the shoreline extent of emergent bulrush (Scirpus lacustris), which is consistent with past studies and underlies the importance of protecting emergent vegetation in efforts to conserve Western Grebes. Grebe abundance also was positively correlated with a longer shoreline perimeter, but was inversely correlated with the amount of forested backshore, which occurred on lakes primarily at the northern margins of Western Grebe range. The amount of backshore development was positively associated with Western Grebe abundance, which might reflect a preference for similar lake characteristics by humans and grebes. These relationships are important to consider in the context of implementing and managing recovery of the Western Grebe in Alberta.